Protection of trade secrets in polish and european legislation - Piotr Widerski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Trade secrets are valuable business assets to all companies on the market irrespective of their size and sector. Empirical evidence prompts clear dependency between innovation and trade secret protection (Ec.europa.eu, 2013). Trade secrets represent the results of R&D investments, innovation and creativity. They are often located as the decisive element of economic advantage in business relationship. The lack of sufficient legal protection of secrets reduces confidence of business creators, researchers and innovators. A current state of protection in the EU has proven to be inadequate to create a satisfactory level of entrepreneurship. Directive 2016/943 endorses a minimum standard requirement for the EU legislation but the Member States may introduce to their own legal systems more far-reaching protection against unlawful acquisition, use or disclosure of trade secrets. Trade secrets play an important role in protecting the exchange of know-how between businesses, especially SMEs, and research institutions both within and across the borders of the internal market, in the context of research, development, and innovation. Trade secrets are one of the most commonly used forms of protection of intellectual creation and innovative know-how by businesses, yet at the same time, they are not sufficiently protected by the existing European Union legal framework.